Immunological Features of Paranasal Sinus Mucosa in Patients with Graves’ Orbitopathy - Lu, Yi; Wu, Yu; Huang, Yazhuo; Fang, Sijie; Li, Yinwei; Sun, Jing; Zhou, Huifang (Frontiers in Endocrinology, 2021)
Background: Previous studies showed that patients with Graves’ orbitopathy (GO) had concomitant mucosal abnormality within the paranasal sinuses. It remains unknown whether the immunological reactions in sinus mucosa affect the orbit inflammation in GO. Methods: Patients with GO scheduled for orbital decompression surgery had underwent sinus computed tomography (CT) scans rated for sinus mucosal disease by two independent reviewers using the Lund-MacKay systems. Ethmoid mucosal samples were collected from orbital decompression surgeries in patients with GO and correction surgeries in patients with old orbital fracture as controls. Histological analysis and immunofluorescence were performed in all sinus mucosa tissues. Flow cytometry analysis was used to examine the immunological features of sinus mucosa in both GO and control groups. Results: Immunohistochemistry showed that the paranasal sinus mucosa of patients with GO grew swelling, with goblet cell and small vessel proliferation, endothelial cell swelling, and inflammatory cell infiltration. The number of helper T helper (Th)1, Th17, and gamma-delta T cells in nasal sinus mucosa of patients with GO increased significantly compared with controls. In addition, there was a decreased number of regulatory T cells in patients with GO. Further, the number of Th2 cells showed no significant difference in those two groups. The proportion of interleukin-22-producing cell subsets in gamma-delta T cells of patients with GO was significantly increased compared with controls. Conclusions: Our observations illustrated a potential pathogenic role of mucosal infiltrating lymphocyte, which may have the possibility to take part in the pathogenesis in GO.